O discurso jurídico sobre pornografia de vingança no Brasil - Silva, Sirlanda Maria Selau da (Universidade do Vale do Rio dos Sinos, 2016)
The revenge porn will be analyzed starting by speeches that have been process in Brazilian judiciary, in especial civil lawsuit that find tutelar rights and obligations, experienced to inviduals envolved on these events. By this perspective, the revenge porn is taken as a committed, whereby close images shared on cyberpace, without the holder consent, in order to foist him constraints, humiliations and other violation the sphere of his personality. As appears from the events analyzed in the course of research, this practice arises due the end of relationship. Of affective and/or sexual order, general rule, focus in men and women relations. These perspectives, the revenge porn, take similarity with other events falling into a relational logical violence gender. As well as an project control of sexuality in various aspects. So, legal speeches about revenge porn will problematised these two perspectives. The ethnography documents - court lawsuits - was adopted as a perspective of analyzes, whereby makes possibile the access to these particular speech: The legal speeches, which is crossed by several circular speeches, on and off to court lawsuit.
Keywords: Discurso; Pornografia de vingança; Violência; Direitos; Sexualidade; Speech; Revenge porn; Violence; Rights; Sexuality; ACCNPQ::Ciências Humanas::Sociologia